Anthropological and Historiographical Research in the Theatre Discipline - Josiah Adewale Apalowo; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
This essay explores the interdisciplinary nature of theatre studies, focusing on integrating anthropological and historiographical research in the discipline. It examines how these approaches contribute to a deeper understanding of theatre as both a cultural and historical artefact. The essay begins by discussing the role of ethnography in theatre, highlighting its ability to uncover the cultural contexts and lived experiences embedded in performances. It also delves into cultural performance theory, emphasizing how theatre acts as a form of social commentary and creates cultural norms. Historiographically, the essay considers theatre as a historical text that reflects the political, social, and cultural climates of its time. It also addresses revisionist historiography, which seeks to challenge traditional narratives and bring marginalized voices to the forefront of theatrical history. Additionally, the importance of archival research is explored, particularly in preserving the ephemeral nature of performances. The intersections between anthropological and historiographical approaches are discussed, revealing how these methodologies complement each other in constructing a comprehensive narrative of theatre's role in society. The essay concludes by asserting that these interdisciplinary approaches are essential for uncovering the rich layers of meaning within performances, contributing to a more inclusive and diverse understanding of theatre history. This research underscores the importance of context in theatrical analysis and the role of theatre in shaping and reflecting humans.